RANCANG BANGUN ALAT UKUR PH DAN SUHU BERBASIS SHORT MESSAGE SERVICE (SMS) GATEWAY - Astria, Fanny; Subito, Mery; Nugraha, Deny Wiria (MEKTRIK)
pH and temperature measuring system devices based on SMS gateway is a measurement tool that communicates with the provider, so it can be used to monitor the pH level and temperature of the water in the distance. It works by using a pH sensor and a temperature detector. pH and temperature measuring devices based on SMS gateway can measure the pH level of the water with a scale between pH 0 to pH 14, whereas for temperature, it can be measured with a scale between -100C up to 1000C. To create this system, it is needed wavecom modem for making a communication with the provider, the pH and temperature sensor as a detector, and ATMega 128 as a controller. This systems is programmed by using Delphi 7 ​​and micropascal application. It is designed during this study a pH and temperature measuring instrument based on SMS gateway and SMS (Short Message Service) as a medium for transferring the information through a long distances. Measurement data can be viewed directly in the LCD of the pH and temperature module. Moreover, it can also be viewed remotely via a PC connected to the modem wavecom and on a mobile phone . Keywords: pH Sensor , Temperature Sensor , SMS (Short Message Service) Gateway .